Clash of the Wolves - Marks, Martin (More Treasures from American Film Archives, 2004)
This is the famous Rin Tin Tin adventure in which the canine star is forced to wear false chin whiskers and leather booties in order to elude the law. That the dog manages to keep a straight face, so to speak, is proof positive that he was a great actor. Rinty's performance in this Warner Bros. silent melodrama set in the California desert is certainly more subtle than that of villain Pat Hartigan, who all but sneers and hisses while contemplating how to jump Charles Farrell's borax claim, not to mention leading lady June Marlowe. "Clash of the Wolves", despite some deterioration, remains a beautifully photographed action thriller that still manages to entertain, and "Rinty's much vaunted thespian capabilities are much in evidence. The dog (or his stunt doubles) at various times acts wounded, happy, ferocious and, yes, even romantic with his canine leading lady, Nanette." Rinty's human co-stars, with the exception perhaps of the aforementioned Mr. Hartigan, do equally well, Charles Farrell giving an early proof of why he later became to important to both Fox and frequent co-star Janet Gaynor. [All Movie Guide]